Gender representation portrayed through emotion characters in “Inside Out” - Dewi Meyrasyawati, Yana Titika, Nurul Fitri Hapsari, (Opción, 2020)
The term gender has become social and cultural construction in the society. However, this gender construction is still unrecognized by children because they are passive in sexual orientation. This study aims to prove that the Disney Pixar‟s film, Inside Out, happens to construct gender representation in the five emotion character figures towards children as the main audience of this film. This study uses qualitative method, specifically on the textual research as the method of study. The conclusion from this research is that not only the film supports the traditional belief between gender roles, but also makes some challenge of gender role on specific characters.